Serum concentrations of apelin-17 isoform vary in accordance to blood pressure categories in individuals with obesity class 3 - Luis Javier Cano Martínez; Ramón Mauricio Coral Vázquez; Juan Pablo Méndez; Silvia Trejo; Juan Carlos Pérez Razo; Patricia Canto (Clinical and Experimental Hypertension, 2019)
Background: The aim of this study was to investigate if serum concentrations of apelin-36, apelin-17, apelin-13 or apelin-12 were different in obesity class 3 individuals with hypertension, when compared to those without hypertension (normal or high-normal). Subjects and Methods: Twenty six individuals with obesity class 3-related hypertension and thirty three individuals without hypertension, who were divided in individuals with normal (n = 23) or with high-normal (n = 10) blood pressure (BP) were analyzed. All individuals presented obesity class 3, without diabetes mellitus. Measurements of all apelin isoforms were performed using enzyme-linked immunosorbent assay kits. Analysis of differences between groups of Apelin isoform concentrations was performed by a One-way ANOVA, with a Tukey test post hoc. Results: The individuals of the hypertensive group presented a slightly lower serum concentration of all apelin isoforms, but these differences were not statistically significant. These results were more evident when the group of patients without hypertension were divided based in normal and high-normal BP, observing that apelin-17 isoform were higher in individuals with high-normal BP in comparison to subjects with normal BP (P = 0.018); concentrations were also higher when compared to subjects with hypertension (P = 0.004). Conclusions: To our knowledge, this is the first study regarding the differences of apelin-17 isoform concentrations in individuals pertaining to different categories of BP, who presented obesity class 3. The group of patients that presented hypertension showed a lower concentration of all isoforms. This observation could be due to the fact that these patients were taking antihypertensive medication.